Factors influencing career growth at intellectual Property Corporation of Malaysia (MyIPO) - Mohd.Nor Hafiz, Abd.Munir (2021)
Career growth is an important factor and should be a priority for all employees. This study aimed to identify the relationship between informal workplace learning, mentoring and leadership towards career growth in Intellectual Property Corporation of Malaysia (MyIPO). Hence, the main objective of this study is to examine factors that influence career growth of the employees in the Intellectual Property Corporation of Malaysia (MyIPO). Generally, the study focuses on determining whether informal workplace learning, mentoring and leadership influence career growth. The 208 respondents who participated in this study were employees of Intellectual Property Corporation of Malaysia (MyIPO). The result of study showed that informal workplace learning, mentoring and leadership influencing have a significant influence on career growth among employees in Intellectual Property Corporation of Malaysia (MyIPO). The findings of this research are valuable, to help in the management of employee career growth. The Intellectual Property Corporation of Malaysia (MyIPO) should incorporate various best practices in informal workplace learning, mentoring and leadership to help its employees achieve positive career growth. Some suggestions for improvement in term of practice are also discussed such as organisation needs to enhance career growth in the future